A Z-scheme 2D/0D ZnIn2S4/ZnO heterostructure for efficient photocatalytic degradation of tetracycline: energy band engineering and morphology modulation. Issue 2 (2nd December 2022) - Wang, Ru; Xie, Xiaoyu; Xu, Chunxiang; Ji, Rendong; Shi, Zengliang; Cui, Qiannan; Wang, Mingliang
Abstract : A hierarchical 2D/0D ZnIn2 S4 /ZnO heterostructure with a Z-scheme energy band configuration was fabricated for the efficient degradation of tetracycline. Abstract : Semiconductor-based photocatalysis is of great practical significance to degrade persistent organic pollutants (POPs). However, it still faces challenges and always in pursuit to construct a photocatalyst system with efficient charge separation and strong redox capacity. Herein, a Z-scheme energy band configuration in a hierarchical heterostructure composed of two-dimensional (2D) ZnIn2 S4 nanosheets and zero-dimensional (0D) ZnO nanoparticles was fabricated for the degradation of tetracycline (TC)—one of the typical POPs. On the one hand, the Z-scheme heterojunction inhibits the recombination of charge carriers and preserves the strong redox capacity of ZnIn2 S4 and ZnO. On the other hand, the hierarchical microstructure and the 2D/0D subunits endow the ZnIn2 S4 /ZnO photocatalyst with good light harvesting, intimate interface contact, and short charge transfer. As a result, the hybrid photocatalyst exhibited a high reaction rate constant of 0.074 min −1 for TC degradation, which is 5.4 and 2.8 times that of the pure ZnIn2 S4 and ZnO, respectively. This work provides new insight into the integration of energy band engineering and morphology modulation to design advanced photocatalytic systems for POP treatment.